QRIS' Impacts on Turnover Based on Business Scale and Sectoral Study on MSME - Sholikhah, Taufiq Hidayati; Soesilo, Nining I. (International Journal Labs, 2023)
In order to improve the efficiency and effectiveness in transactions of various non-cash payment channels, it is necessary to have an infrastructure that is able to integrate transactions originating from debit cards, credit cards, and electronic money in one door, through the standardization of the Quick Response Code (QR Code). In this paper, it will evaluate the impact of the implementation of the QRIS standardization policy on Malaysian Small and Medium Enterprises (MSMEs) turnover based on the business scale and economic sector of the business. The research was conducted by observing two groups, namely, the treatment group (UMKM using QRIS) and the control group (umKM not using the policy) in two time periods namely before and after the adoption of the policy. The test results per business sector showed significant results for the whole, micro-scale as well as processing/secondary economic sectors where there was a significant positive impact (P0.5) affecting turnover growth in MSMEs that adopted QRIS, compared to those that did not adopt QRIS. The QRIS implementation program can be continued and expanded in scope.